Business Process Reengineering (BPR) Pada Penerbitan Buku di UPT. Universitas Mataram Press - Ruslan Yusuf (Jurnal Repositor, 2023)
UPT. Mataram Press University is one of the Technical Service Units (UPT) at the University of Mataram. One of the service units, namely Book Publishing, which is the focus of this study, found several service problems in business processes, especially in terms of service. So it is necessary to evaluate business processes to improve service quality. So it is proposed to carry out business process reengineering using the Business Process Reengineering (BPR) method. Business Process Reengineering is a method or concept to change business processes in an organization that has weaknesses in its business processes to make it more efficient and competitive. The design process with all processes uses the ASME (American Society of Mechanical Engineering) standard map to make it easier to design business processes. Business process improvement using ESIA Techniques. At UPT. At the University of Mataram Press, there are two business processes that have been improved, namely the book publishing process and the data publishing reporting business process. Each business process is tested for efficiency using a throughput efficiency test with the results of the initial book publishing process being 50% and the process recommendation increasing by 95.4% with a total time of 63424 minutes. The results show an increase in efficiency and can maximize performance on business process recommendations at UPT.Universitas Mataram Press. Keyword: System Reengineering, Business Process Reengineering, Book Publishing, ASME Standard Mapping, throughput efficiency test.